History of the Development of Hindu Academic Culture at IAHN Tampung Penyang Palangkaraya: Adaptation of Local Dayak Values in Higher Education - Nurlensi Nurlensi (KASTA : Jurnal Ilmu Sosial, Agama, Budaya dan Terapan, 2026)
The establishment of the Tampung Penyang State Hindu Institute in Palangka Raya represents a historical response to the Dayak community's need for a higher education institution capable of bridging the gap between the demand for state recognition of Hinduism and the desire to maintain Kaharingan cultural identity. This study aims to explore in depth the historical development of Hindu academic culture at IAHN Tampung Penyang Palangkaraya, focusing on the process of adapting Dayak local wisdom within the context of higher education. The method used is a literature study, with data sources consisting of books, scientific journal articles, and relevant research reports. The research findings reveal four main findings. First, the historical and ideological foundation of the establishment of IAHN Tampung Penyang Palangkaraya was built on a harmonious meeting point between the Dharma Agama Hindu and the Huma Betang philosophy as a cultural strategy to ensure that Hindu education is not uprooted from its traditional Dayak roots. Second, the manifestation of local Dayak values in the curriculum and academic traditions took place through a hybridization process between the Hindu Gurukula system and Dayak communal norms, creating a distinctive Hindu Nusantara epistemology. Third, IAHN Tampung Penyang Palangkaraya evolved into a Cultural House that plays a vital role in preserving and reactualizing Hindu-Dayak identity through scientific production and intellectual diplomacy. Fourth, this institution faces challenges in the form of potential clashes between academic rationality and customary sacredness as well as the impact of globalization on the younger generation, which are responded to through adaptive strategies in the form of affirming cultural identity, strengthening customary cooperation, and cultural advocacy.